Baseball's greatest hitters - Kramer, Sydelle; Campbell, Jim, 1942- (New York : Random House, 2003)
Brief profiles of such hard-hitting baseball players as Barry Bonds, Ty Cobb, Babe Ruth, Ted Williams, and Hank Aaron.
Keywords: Baseball players -- United States -- Biography -- Juvenile literature; Batting (Baseball) -- Juvenile literature; Baseball players